The Linguistic Representation of Social Hierarchy and Kinship in Chibi Maruko-chan - Sari, Al Mustika; Muhid, Abdul; Syahid, Agus (LPPM Universitas Bumigora Mataram, 2025)
This qualitative descriptive study examines the linguistic representation of social hierarchy and kinship in the Japanese animated series Chibi Maruko-chan. Grounded in sociolinguistic theories of politeness and indexicality, the research investigates how language constructs familial and social roles within the show’s narrative framework. The primary objectives are to identify and categorize specific linguistic features—including honorifics, address terms, and politeness strategies used to denote social relationships—and to analyze how these discursive practices reinforce traditional Japanese concepts of uchi (in-group) and soto (out-group). Data were collected through purposive sampling of fifteen episodes, forming a corpus of dialogue that was subsequently analyzed using directed content analysis. The findings reveal a consistent asymmetry in politeness strategies: children, particularly the protagonist Maruko, predominantly use positive politeness and casual language to express closeness, while parents and older siblings employ negative politeness, formal self-reference, and bald-on-record directives to assert authority and maintain hierarchical order. Interactions with grandparents blend affection and respect, softening hierarchical boundaries, whereas peer interactions exhibit egalitarian solidarity through direct, unmitigated speech. The study concludes that the series actively naturalizes social structures through everyday talk, serving as a rich site for the discursive reproduction of cultural norms. It contributes to media linguistics by demonstrating the value of anime as a corpus for pragmatic analysis and offers insights into the intersection of language, power, and culture in popular media.